Perception of learning, satisfaction and self-efficacy of nursing students about High-Fidelity Simulation - Duarte, Hugo Miguel Santos (2018)
Background Over the last years the teaching of nursing has been progressively directed to the use of new methodologies, among which we highlight the High-Fidelity Simulation (HFS), which allows nursing students to have their first contact with the clinical practice within the academic environment. Objective: To evaluate and correlate the perception of learning, satisfaction and self-efficacy of nursing students about HFS. Methods A correlational study with 139 nursing students was developed, using the Portuguese version of the Nursing Students’ Perceptions of Learning and Learner Satisfaction with Simulation Tool. Results Nursing students reveal a moderated perception of learning about the HFS (3.649 ± 0.513 out of 5 points), a good level of satisfaction (7.317 ± 1.065 out of 10 points) and a self-efficacy for the practice of HFS (31.590 ± 3.974 out of 40 points). All correlations between perception of learning, satisfaction and self-efficacy of the students regarding HFS were positive and highly significant (p ≤ 0.001), with values between 0.991 and 0.385. Conclusions This study reveals that nursing students are satisfied with the practice of HFS, as well as shows a positive perception of learning and self-efficacy about HFS. The fact that the correlations among these three variables are highly significant and positive, demonstrate the importance of the practice of HFS within the school environment, which allows the development of experiences of high value for the nursing students.